Insider Trading Analysis of the Indonesian Capital Market - Hardicky, Nilvany (Jurnal Indonesia Sosial Sains, 2024)
Insider trading is one of the crucial issues in the capital market that can have a significant impact on market integrity and stability. In Indonesia, the practice of insider trading not only causes losses for investors who do not have access to insider information but can also reduce investor confidence in the capital market as a whole. Research This article will analyze and explain Insider Trading in the Indonesian Capital Market. This study uses notative juridical methods or normative law. The results of this study explain that Insider Trading in the Indonesian Capital Market is contained in Articles 95, 96, 97, 98, 99, and Article 104 which explain that insiders from an issuer of public companies that have inside information are prohibited from buying or selling affects, or companies that make transactions with issuers where they work. The prohibition on the use of insider information is more due to unfair actions against others who are completely unaware of the existence of the information. Investor protection is one very important way because if investors do not get enough protection, they are reluctant to make transactions on the exchange. Without a large number of investors, capital market activities will be weak, and the function of the capital market will not develop, the principle of openness as one of the efforts to protect investors. Such protection efforts will be realized if the implementation of information transparency or full disclosure obligations containing material facts in activities that take place in the capital market in accordance with the purpose of the principle of openness itself, namely to create a fair, efficient and orderly market that protects Investors and helps determine accurate market prices which are all intended for the benefit of Investors or potential Investors.